Pengaruh Ransum Konsentrat Broiler terhadap Performa Ayam Kampung - Aditya Pamungkas; Amani Aldiyanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to evaluate the effect of broiler concentrate-based rations combined with corn and rice bran on the performance of native chickens. A total of four dietary treatments were formulated, namely P1 (100% broiler concentrate), P2 (75% broiler concentrate, 10% corn, 15% rice bran), P3 (50% broiler concentrate, 30% corn, 20% rice bran), and P4 (25% broiler concentrate, 55% corn, 20% rice bran). The parameters observed included feed intake, body weight gain, and feed conversion ratio (FCR). Data were analyzed using analysis of variance (ANOVA), and significant differences among treatments were further tested with Duncan’s New Multiple Range Test (DMRT). The results showed that dietary treatments significantly affected the growth performance of native chickens (P<0.05). Chickens fed diets with higher proportions of broiler concentrate (P1 and P2) exhibited better body weight gain and more efficient feed conversion compared to those receiving lower concentrate levels (P3 and P4). In contrast, increasing corn and rice bran levels tended to increase feed intake but did not proportionally improve body weight gain, resulting in poorer FCR. It can be concluded that native chickens perform optimally when fed rations containing at least 75% broiler concentrate, which provides a balance between growth and feed efficiency.